Answer:
-2 and 6
Explanation:
Mark the first number as x
and the second number as y
Since x + y = 4
y = 4 - x
// substitute the given value of y into the equation
- 3xy = 76
+
- 3 * x * (4 - x) = 76
+ 16 - 8x +
- 12x + 3
= 76
+
+ 3
- 20x = 76 - 16
5
- 20x = 60
5
- 20x - 60 = 0
// divide both sides by 5
- 4x - 12 = 0
// write -4 x as a difference, this way it is faster than calculating discriminant
+ 2x - 6x - 12 = 0
// factor out x and -6 from the expression
x (x +2) - 6 (x +2) = 0
(x - 6) * (x + 2) = 0
// there are two possible cases
1) x - 6 = 0
2) x + 2 = 0
1) x = -2
2) x = 6
// substitute the given value of x into the equation
1) y = 4 - x = 4 - (-2) = 6
2) y = 4 - x = 4 - 6 = -2
Now we get two pairs (-2; 6) and (6; -2), which are the solutions to the system
Since their sequence as the question suggests is irrelevant, the numbers are -2 and 6